Bioactive Compounds, Phytochemical Composition and Health-Promoting Properties of Cicer arietinum L: A Comprehensive Review - Ramesha K. Lakshmaiah; Shivakumar Venkataramaiah; Devaraja Sannaningaiah (Advanced International Journal for Research, 2026)
Cicer arietinum L. (chickpea) is a valuable source of nutrition comprising various bioactive compounds. The seeds of this legume plant are a rich source of protein, carbohydrates, fiber, minerals, vitamins and unsaturated fats. They also contain phenolic acids, flavonoids, saponins, tannins, carotenoids and other phytochemicals. The bioactive compounds found in chickpeas are promising due to their antioxidant, anti-inflammatory, antidiabetic, cardioprotective, anticarcinogenic and gastroprotective effects. Researchers have proved the ability of chickpeas to improve glucose and lipid metabolism, as well as intestinal function and reduce oxidative stress and inflammation. So that, this legume product can be considered a functional food with a noteworthy impact on human health, particularly in the prevention of chronic diseases. However, the processing methods, including soaking, germination, cooking, roasting, fermentation, and milling, can significantly affect the composition and content of phytochemicals. Despite the existing data on the impact of C. arietinum on human health, it is necessary to conduct further studies. In particularly, the need for deep understanding of the physiological effects. Besides, it needs to be analyzed the impact of most common processing technologies on the chemical composition of chickpeas.